Prescription of healthy ecology. Review on the monograph of Beletskaya E.N., Onul N.M. «Ecological-hygienic assessment of technogenic load caused by the environment as a risk factor for health of population of Pridneprovye». – Dnepropetrovsk: Accent PP, 2 - Korobchansky, V. A. (Medicni Perspektivi, 2016)
Prescription of healthy ecology. Review on the monograph of Beletskaya E.N., Onul N.M. «Ecological-hygienic assessment of technogenic load caused by the environment as a risk factor for health of population of Pridneprovye». – Dnepropetrovsk: Accent PP, 2016. – 140 p.